Rosacea: An Overview of Its Etiological Factors, Pathogenesis, Classification and Therapy Options - Serap Maden (MDPI AG, 2023)
Rosacea is a common chronic inflammatory skin condition. It mainly affects the cheeks, nose, chin, and forehead, causing flushing or transient erythema, persistent erythema, phymatous changes, papules, pustules, and telangiectasias, and the eyes may also be affected by rosacea. Rosacea is more common in women than in men and can start at any age. Rosacea affects both fair-skinned and darker-skinned people. Physical changes in the face due to rosacea can cause embarrassment, leading to reduced quality of life and self-esteem. Rosacea has several triggers, and its pathogenesis involves multiple factors, which means there are several treatment options, and these options can be combined. A patient's clinical findings and symptoms will help a doctor to diagnose and classify the condition. Treatment options may include lifestyle changes, topical medications, systemic antibiotics and light-based therapy. The best approach is to tailor the treatment to the individual's condition and preferences. The aim of treatment is to manage symptoms and prevent the progression of the disease.